Pendampingan Belajar Guna Mengurangi Penggunaan Gadget Pada Anak-Anak Di Dukuh Candisari Cepogo Boyolali - Kunasiroh Kunasiroh; Donna Setiawati (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The problem of online learning is not only felt by teachers and students but also by parents. Students complain that it is difficult to understand the lessons given by their teachers while many parents do not have time to accompany their children to study at home because parents are busy working. The purpose of this service activity is to motivate children's enthusiasm for learning so as to reduce the use of smartphones and to improve their Islamic behaviour. The method used is to form study groups and study mentoring. The result of this service activity is that the children in Candisari Hamlet are motivated to study hard and feel helped in completing their school assignments.